2021
DOI: 10.1057/s41278-021-00195-6
|View full text |Cite
|
Sign up to set email alerts
|

Literature review and comparative analysis of inland waterways transport: “Container on Barge”

Abstract: Container on Barge (COB) facilitates intermodal transportation by transporting shipping containers on barge tows. COB has seen rapid expansion globally over the past 20 years, providing a cost-efficient, environmentally friendly, and congestion-reducing mode of container transportation. European countries have led COB transportation in both study and application over the past two decades. However, increasing interest is observed in both the USA and Asia. In this literature review and comparative analysis, 135 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 132 publications
(181 reference statements)
0
10
0
Order By: Relevance
“…For sustainable development of IWT, the assessment of ports infrastructure and equipment to support IWT operations is a priority; this can lead to the construction of intermodal terminals to improve logistics performance or the expansion of main ports in some strategic geographical location, to improve the capacity of cargo collection, distribution, and performance in general (Bu and Nachtmann 2021;Rožić et al 2016;Vilarinho et al 2019). Finally, from a human resources perspective, currently, the is a staff shortage in ports and the requirement for a skilled labour force to support IWT operations (Koralova 2017;Pfoser et al 2018;Vilarinho et al 2019).…”
Section: Ports (Inland River Ports-seaports)mentioning
confidence: 99%
See 2 more Smart Citations
“…For sustainable development of IWT, the assessment of ports infrastructure and equipment to support IWT operations is a priority; this can lead to the construction of intermodal terminals to improve logistics performance or the expansion of main ports in some strategic geographical location, to improve the capacity of cargo collection, distribution, and performance in general (Bu and Nachtmann 2021;Rožić et al 2016;Vilarinho et al 2019). Finally, from a human resources perspective, currently, the is a staff shortage in ports and the requirement for a skilled labour force to support IWT operations (Koralova 2017;Pfoser et al 2018;Vilarinho et al 2019).…”
Section: Ports (Inland River Ports-seaports)mentioning
confidence: 99%
“…In other cases, local governments are responsible for those activities on behalf of the central government (Jiang et al 2018). Regardless of the governance models, several regulations and long-term master plans are required to support IWT's sustainable development; moreover, the participation of public and private sectors is indispensable to stimulate a modal shift from road and rail to IWT (Bu and Nachtmann 2021;Chen et al 2016;Havinga 2020;Malkus et al 2020;Nguyen and Nguyen 2020;Roso et al 2020). Other necessary environmental regulations that include integrated ecological strategies, such as emission reduction and implementing subsidies related to environmental sustainability, are a priority (Barros Cavalcante et al 2020;Mihic et al 2011;Vilarinho et al 2019).…”
Section: Waterwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Others have studied the operation and performance of the inland waterway ports. A detailed literature review of inland waterway transportation can be found in Bu and Nachtmann ( 9 ), Restrepo-Arias et al ( 19 ), Li et al (20), and Witte et al ( 21 ). With regard to research on inland waterway ports specifically, three distinct periods have been identified in Witte et al ( 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inland waterway ports must be utilized with other freight systems to maximize the ports' competitiveness in inland waterborne freight. Inland ports relieve the pressure on coastal ports by managing the distribution workload and alleviating port congestion (9)(10)(11)(12). Moreover, inland ports provide immediate benefits to rural areas by making them attractive to new industries, which creates new employment opportunities for the residents and recreational facilities for the local community (13).…”
mentioning
confidence: 99%